A Study on the Performance of PGI with Reference to West Bengal - Singha, Ishani; Pandey, Nandlal (International Journal of Engineering and Management Research, 2026)
The Ministry of Education created the Performance Grading Index (PGI) to measure the quality of school education in all of India’s States and Union Territories. This study looks at PGI reports to find out why performance varies, what strengths and weaknesses there are, and what factors affect differences between states. The PGI framework examines aspects such as learning outcomes, access, infrastructure, equity, teacher availability, and governance. Recent PGI cycles show significant differences between states. Some perform well due to strong governance and robust infrastructure, while others face challenges such as inadequate teacher availability, low learning levels, and limited resources. The study highlights the importance of PGI in encouraging evidence-based reforms, accountability, and transparency. It also identifies patterns, gaps, and opportunities for targeted interventions that can improve education across the country. This study further examines methods to enhance West Bengal’s Performance Grading Index by benchmarking it against higher-performing states in India. PGI evaluates parameters such as access, infrastructure, equity, teacher management, and governance. The study identifies specific strategies for improvement by analysing best practices from other states. These include enhancing teacher professional development, expanding digital and classroom infrastructure, improving early grade learning programs, and implementing data-driven governance. If these changes are implemented, West Bengal’s PGI performance can improve significantly, along with the overall quality of education in the state.